Constituents and Drivers of Mission Engagement for Social Enterprise Sustainability: A Systematic Review. (March 2022) - Kulshrestha, Reeti; Sahay, Arunaditya; Sengupta, Subhanjan
Social entrepreneurship as a prosocial phenomenon focuses on the upliftment of the vulnerable and marginalised through entrepreneurship. Social enterprises are mission-oriented often suffering from mission-related challenges that accompany duality in its form. This in turn raises concern over sustainability for social enterprises as they begin to focus more on the economic objectives rather than the social value they originally intended to create. The objective of the study is not only to carry out a systematic literature review of the mission of a social enterprise but to also come out with drivers of mission engagement that contribute to social enterprise sustainability. Drawing upon past literature covering vast databases like Scopus and Proquest, and our understanding from reputed ABDC listed journal articles, we propose a conceptual framework of mission engagement for social enterprise sustainability that offers a fresh perspective on mission duality. We make a three-fold contribution to social entrepreneurship literature with a categorisation of literature for better conceptual clarity on mission-related concepts in social entrepreneurship, four constituents of mission engagement in social enterprises and three drivers to creating a sustainable social enterprise through mission engagement. We propose the notion of 'sustainable social enterprises', which derives maximum benefit from cross-sectoral collaboration, active engagement in building strong social networks and building on social capital to bring about transformative societal change.